2017
DOI: 10.17235/reed.2017.4699/2016
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of submucosal tunneling endoscopic resection and endoscopic full-thickness resection for gastric fundus submucosal tumors

Abstract: Results: A total of 43 patients were enrolled: 15 underwent STER and the remaining 28 cases underwent EFTR. There were no significant differences between the two groups with regard to gender, age, tumor size, en bloc resection rate, operation time, pathohistological results and cost (p > 0.05). However, patients who underwent EFTR had a longer suture time, required a larger number of clips for closure and a prolonged postoperative hospital stay (p < 0.05). No recurrence was noted in either the STER or the EFTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…However, surgical resection, regardless of whether open surgery or video-assisted thoracoscopic surgery (VATS) is performed, seems to be more invasive than endoscopic resection[35-38]. STER is regarded as the optimum method for resecting SMTs originating from the MP layer based on its advantages of a high en bloc resection rate and the ability to maintain the integrity of the mucosa[29,39-41]. The creation of a tunnel not only maintains the integrity of the mucosa, but also decreases the likelihood of perforation, postoperative infection, fistula, and stricture[12].…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical resection, regardless of whether open surgery or video-assisted thoracoscopic surgery (VATS) is performed, seems to be more invasive than endoscopic resection[35-38]. STER is regarded as the optimum method for resecting SMTs originating from the MP layer based on its advantages of a high en bloc resection rate and the ability to maintain the integrity of the mucosa[29,39-41]. The creation of a tunnel not only maintains the integrity of the mucosa, but also decreases the likelihood of perforation, postoperative infection, fistula, and stricture[12].…”
Section: Discussionmentioning
confidence: 99%
“…However, because GISTs are more fragile compared to other submucosal tumors and resection with an intact capsule is technically more challenging, additional surgery and monitoring should be considered if piecemeal excision occurs or pathology reveals GISTs with high-risk features. 11 , 12 Further prospective studies are needed to establish the role of STER in larger submucosal tumors.…”
Section: Case Descriptionmentioning
confidence: 99%
“…When compared with endoscopic mucosal resection and ESD, STER has been associated with a lower rate of complications 82. Last, when STER has been compared with endoscopic full-thickness resection, another minimally invasive means of SMT resection, studies have shown that the clinical outcomes are again relatively similar, but that STER was associated with decreased suture time, smaller number of clips used to close the incisions,86 and shorter hospital stay 87…”
Section: Submucosal Tunneling Endoscopic Resection (Ster)mentioning
confidence: 99%